2012
DOI: 10.3329/jhpn.v30i1.11272
|View full text |Cite
|
Sign up to set email alerts
|

Internalized HIV/AIDS-related Stigma in a Sample of HIV-positive People in Bangladesh

Abstract: Internalized stigma among people living with HIV/AIDS (PLHA) is prevalent in Bangladesh. A better understanding of the effects of stigma on PLHA is required to reduce this and to minimize its harmful effects. This study employed a quantitative approach by conducting a survey with an aim to know the prevalence of internalized stigma and to identify the factors associated with internalized stigma among a sample of 238 PLHA (male=152 and female=86) in Bangladesh. The findings suggest that there is a significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
39
5
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 19 publications
6
39
5
7
Order By: Relevance
“…The questions posed to participants as part of this questionnaire were first prepared in English and then translated into Bengali. The questions on discrimination experiences and internalized stigma were created by review of previous studies [15,16]. Five questions with either "yes" or "no" as the possible answer assessed discrimination experiences resulting from obstetric fistula during the previous 6-month period.…”
Section: Methodsmentioning
confidence: 99%
“…The questions posed to participants as part of this questionnaire were first prepared in English and then translated into Bengali. The questions on discrimination experiences and internalized stigma were created by review of previous studies [15,16]. Five questions with either "yes" or "no" as the possible answer assessed discrimination experiences resulting from obstetric fistula during the previous 6-month period.…”
Section: Methodsmentioning
confidence: 99%
“…Such mentality existing in the HIV-free population was highlighted by others as well. 9,16,19,[25][26][27][28] A few participants reported of depression and one had a suicidal tendency, so HIV-associated discrimination could be a serious cause of depression. A study in Thailand showed that emotional and social support was inversely related to depression and directly related to stigma.…”
Section: Discussionmentioning
confidence: 99%
“…8 Stigma is a major barrier for the successful treatment of the PLWHA worldwide as highlighted by a number of studies. [9][10][11][12][13][14][15][16][17][18] We report the first study related to stigma in the North Karnataka Region of India, which is one of the most underdeveloped areas of the state and has a high prevalence of HIV/AIDS.…”
Section: 5005/jp-journals-10024-2123mentioning
confidence: 99%
“…Stigma pada HIV/AIDS muncul proses internalisasi terkait pada suatu penyakit yang tidak dapat disembuhkan dan berujung pada kematian. Stigma juga timbul karena kurangnya paparan informasi sehingga menyebabkan pengetahuan yang rendah serta adanya rasa takut tertular, dan seiring pemahaman yang berkembang tentang penyakit ini, stigma bergeser pada perilaku high-risk yang dapat menyebabkan seseorang terjangkiti virus tersebut dan juga dipandang tidak bermoral, sehingga para ODHA dirasa patut untuk menderita penyakit mematikan ini (Hasan et al, 2012;Waluyo, Culbert, Levy, & Norr., 2014;Yang et al, 2015).…”
Section: Pendahuluanunclassified